Pengaruh Kepemimpinan, Motivasi Kerja, Kompensasi Terhadap Efektivitas Kerja Pegawai Dengan Profesionalitas Dan Kepatuhan Sebagai Variabel Intervening (Studi Kasus Pengembangan Sumber Daya Manusia di Lingkungan Bawaslu Kota Tanjungpinang) - HENDRI SAFUTRA (Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
The Tanjungpinang City Election Supervisory Agency, as an organization, is faced with the challenge of completing its work within a limited time frame and meeting the expectations of many parties. This study aims to provide a comprehensive picture related to how the correlation between independent variables of leadership, motivation, and compensation to the dependent variable of performance effectiveness mediated by two intervening variables, namely: compliance and professionalism variables. The method used in this study uses a quantitative method with a partial least square approach. Furthermore, this study uses primary data taken using the total sampling method. The results of the study showed a significant p value below 0.05 in all variables indicating that there is a strong relationship between these factors and employee performance. Furthermore, the high T value for the motivation and leadership variables indicates that these two factors are very important in increasing work effectiveness, especially in the context of human resource development in the public sector. In addition, the relatively low standard deviation indicates that employee performance estimates are stable across samples, indicating that the interventions carried out can be applied consistently across various organizational contexts. This study has limitations in terms of the limited number of samples. Therefore, this study can be further developed in the future by conducting a critical evaluation of the methodology and sampling techniques used.